2015
DOI: 10.2169/internalmedicine.54.4022
|View full text |Cite
|
Sign up to set email alerts
|

Severe Insulin-resistant Diabetes due to Insulin Antibodies Associated with Eosinophilia

Abstract: A 66-year-old man with type 2 diabetes on hemodialysis treatment was admitted due to poor glycemic control. His serum insulin level and the 125 I-insulin binding rate were extremely high with an increased eosinophil count, although he did not have an allergic reaction to insulin or an elevation of specific IgE for human insulin. A Scatchard analysis revealed that the patient's insulin antibodies had a low affinity constant and a high binding capacity. Prednisolone administration decreased the eosinophil count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In those studies, patients' 125 I-insulin-binding rates were measured to assess AIA production. After prednisolone treatment, the 125 I-insulin-binding rate decreased from 54% to 23% [7] and from 83.5% to <4% [19].…”
mentioning
confidence: 89%
“…In those studies, patients' 125 I-insulin-binding rates were measured to assess AIA production. After prednisolone treatment, the 125 I-insulin-binding rate decreased from 54% to 23% [7] and from 83.5% to <4% [19].…”
mentioning
confidence: 89%
“…Some studies have reported cases of severe insulin resistance (IR) secondary to insulin antibodies, with several treatment methods showing some success . Herein, we report on a 58‐year‐old Chinese woman with a 14‐year history of type 2 diabetes with severe diabetic ketoacidosis (DKA) due to insulin antibodies.…”
mentioning
confidence: 99%
“…As such, temporal reduction of insulin-binding IgG did not accompany the amelioration of clinical signs. In human study, severe insulin-resistant diabetic patients with AIA production have been reported [ 7 , 19 , 21 ]. In those studies, patients’ 125 I-insulin-binding rates were measured to assess AIA production.…”
mentioning
confidence: 99%
“…In those studies, patients’ 125 I-insulin-binding rates were measured to assess AIA production. After prednisolone treatment, the 125 I-insulin-binding rate decreased from 54% to 23% [ 7 ] and from 83.5% to <4% [ 19 ]. Meanwhile, non-insulin-resistant diabetic patients exhibited 125 I-insulin-binding rate <10% [ 21 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation